The Study of Standard Operating Procedures (SOP) Implementation of Vehicle Rental Service Providers in Bali - Fahmadi, Aat Eska; Srianto, Srianto; Kurniawan, Moch Aziz (Asian Journal of Logistics Management, 2022)
This paper examines how vehicle service companies in Bali have implemented their work and operational requirements. This study aims to find out whether vehicle service providers have implemented Standard Operating Procedures for tourists in Bali. This research is a descriptive research. The sample in this study were 42 service providers spread across the island of Bali.  The data collection methods was simple random sampling while the data analysis using content analysis. According to the authors' data, only 18 (43%) of the companies that provided motor vehicle rental services had operational standards (SOP), while the other 24 (57%) either lacked them or couldn't prove they existed. 18 or more of these service providers, many of which merely verbally convey it. Other than that, there is still a gap between the work done by the 18 service providers and what is done in practice, such as when permits are issued to foreigners who lack an international license, carry a false identity, or give a permissions to Underage foreigners. There is no legal framework that regulates the SOP for vehicle rental. So that makes the existing SOP very diverse. The legal framework regarding standardization of policies, regulatory requirements for motor vehicle leasing should be regulated by one of the policy makers, in this case the government.